Translation and Linguistic Validation of Korean Version of the Expanded Prostate Cancer Index Composite for Clinical Practice for Patients With Prostate Cancer - Young Cheol Hwang; Sung Yong Cho; Ja Hyun Ku; Seong Jin Jeong; Seung-June Oh (International Neurourology Journal, 2021)
Purpose Advances in the diagnosis and treatment of prostate cancer have increased the patients’ stress level and decreased the quality of life. A variety of instruments are currently available to evaluate patients with prostate cancer. However, only a few tools are available to assess Korean patients, and therefore we demonstrated a linguistic validation of Korean Expanded Prostate Cancer Index Composite for Clinical Practice (EPIC-CP). Methods EPIC-CP was translated into Korean and the linguistic validation was evaluated. The evaluation process includes permission for translation, forward translation, reconciliation, backward translation, cognitive debriefing, and proofreading. Two bilingual translators independently translated the original questionnaire, discussed the feasibility and naturalness of initial translation, followed by revision to the reconciled version. Another translator then performed a backward translation into English. Ten patients with prostate cancer completed the translated questionnaire and performed cognitive debriefing. Results The original EPIC-CP was translated into 2 Korean versions. The different wording in both versions and the ordinary words in the initial translations were changed considering the nuances and meanings of medical terms. During the backward translation, the panels made slight changes to clarify the meaning and nuances of the translated questionnaire. During cognitive debriefing, 10 patients answered the questionnaire and offered their opinions regarding comprehensibility and naturalness. Most patients agreed that the translation was comprehensible in general. Conclusions Our study provides a successful linguistic validation of the EPIC-CP questionnaire. The translation is a helpful diagnostic tool to ensure the quality of life of patients with prostate cancer attending crowded clinics.